BIM determines the number of merocytic dendritic cells, a cell type that breaks immune tolerance. Issue 9 (5th June 2018) - Audiger, Cindy; Lesage, Sylvie
Abstract: In contrast to conventional dendritic cells (cDC), when merocytic dendritic cells (mcDC) present antigens derived from apoptotic bodies, T‐cell anergy is reversed rather than induced, a process that promotes autoimmunity. Interestingly, mcDC are present in higher proportion in type 1 diabetes‐prone NOD mice than in autoimmune‐resistant B6 and BALB/c mice, and the Insulin‐dependent diabetes (Idd)13 locus is linked to mcDC proportion. Therefore, mcDC are notably associated with susceptibility to autoimmune diabetes. To identify which gene determines the proportion and absolute number of mcDC, we undertook a candidate gene approach by selecting relevant candidates within the Idd13 locus. We find that neither β2m nor Sirpa appear to influence the proportion of mcDC. Instead, we show that Bim effectively modulates mcDC number in a hematopoietic‐intrinsic manner. We also demonstrate that Bim ‐deficiency does not impact other cDC subsets and appears to play a specific role in determining the proportion and absolute number of mcDC by promoting their survival. Together, these data demonstrate that Bim specifically modulates the number of mcDC. Identifying factors that facilitate apoptosis of mcDC by increasing BIM activity in a cell type‐specific manner may help prevent autoimmunity. Abstract : Merocytic dendritic cells are associated with increased autoimmune susceptibility. Using a candidate gene‐based approach, we define a new role for Bim in modulating immune tolerance by specifically regulating the proportion and absolute number of merocytic dendritic cells.